DIPLOMASI BUDAYA INDONESIA MELALUI RBI DALAM MENANAMKAN CITRA POSITIF DI JEPANG PADA TAHUN 2017-2020 (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2022)
This research aims to analyze the strategy of Indonesian cultural diplomacy through RBI to instilling a positive image of Indonesia in Japan. One of Indonesia’s diplomacy is shown in Japan by establishing the Indonesian Cultural House (RBI). Japan was chosen to enhance Indonesian cultural diplomacy because Japan has a decent role in the development of Indonesia. Besides that, Japan is also one of the countries that emphasize culture as a national asset. This research draws upon theory of public diplomacy and a concept of cultural diplomacy by using descriptive methods and qualitative approaches. This research found that in implementing cultural diplomacy through RBI, Indonesia’s diplomacy is done in a peaceful circumstance by utilizing several forms of cultural diplomacy such as exhibitions, competitions, and exchanges of experts or studies. Thus, it can establish a positive image for Indonesia, both in the eyes of the Japanese public and the international community.